Bundled plastic optical fiber based sensor for ECG signal detection - Yasin, Moh; Zulkarnaen, M.; Yhuwana, Y.G.Y.; Samian, -; Zaidan, A.H.; Harun, Sulaiman Wadi (Elsevier, 2020)
This study demonstrates the development of a novel low-cost bundled plastic optical fiber (POF) displacement sensor for the measurement of amplitude and frequency of heart rate signal. A compact optical setup is developed in the laboratory for use in the testing. It consists of a fiber optic transmitter, fiber optic bundled probe and photodiode detector, and an electrocardiogram (ECG) simulator as a heart rate signal. The sensitivity of the sensor is found to be 4.6 mV/mm, and thus it is capable of measuring heart rate from 30 bpm to 300 bpm (for the amplitude of ECG at 0.5, 1.0 and 2.0 mV) with linearity of more than 99 %.The results demonstrate that the proposed fiber optic based heart rate sensor is not only easy-to-make, cost-effective and robust but also offers sensitive, stable and high precision heart beat measurements. © 2019 Elsevier GmbH